Plan de fortalecimiento de los canales de comunicación interna como influencia positiva en el mejoramiento del clima laboral en la empresa Ecua-Auto de la ciudad de Quito - Vallejo Zambrano, Vilma Rosario (2014)
The main objective of this research is to develop an -internal communication channels strengthening plan- for ECUA -AUTO SA, based on the needs and organizational structure of the company, in order to improve the work environment for their employees. A suitable working environment in companies promotes motivation and welfare of employees, improving productivity, interpersonal relationships, and thus creating a positive atmosphere that allows to attach them to the company. The research began by exposing the results of an investigation made in the company, on the Quality communication, working environment, efficiency, and corporate culture subjects, among others. One of the fields that returned not encouraging results within the research was communication. This variable yielded that employees had a remarkable unawareness of the company structure and the type of communication held, thus generating dissatisfaction with their tasks, weaknesses of the inner relationships and lack of motivation. As an introduction, an overview ECUA -AUTO SA is shown, where the history, mission, vision, values, organizational structure and a descriptive functional structure are exposed, information that shows its purpose and line of business, as well as its products and services, and the scope of the market in which it operates .Subsequently the basics of organizational culture and their relationship with the current situation are presented. Then the theory for organizational climate and their effects, as well as a breakdown of the current benefits that the company offers to its employees is analysed. All elements of organizational communication and its relation with internal communication in ECUA -AUTO SA are also studied. Finally, a plan to strengthen the channels of communication, including action sub plans has been made as a response to the needs raised by employees within ECUA -AUTO S.A.